Research and forecasting of the market of consumption of pork - Prymuk, Olga; Ustynovych, Natalia; Yaroshok, Valentina (Management and Entrepreneurship: Trends of Development, 2019)
Purpose. The purpose of the article is to study the market for consumption of pork livestock in Ukraine and forecast its dynamics. Design/methodology/approach. In the course of the study, methods of comparison, analysis of statistical data and graphic methods were used. Findings. The subject of the study is the substantiation of the volume of consumption of pork in the meat market of the country and the identification of its factors. Рork is a very promising industry that is developing dynamically. A number of companies plan to increase the stock, opening new pig farms on their farms. Therefore, the issue of studying the market situation of consumer consumption of pork is relevant, taking into account the perspective expectations of its growth in large farms with vertical integration. The main factors influencing the dynamics of the number of livestock are: the outbreak of African swine fever; reduction of demand in the domestic market; reduction of state support to the pig industry; export of pork. Over time, the pork market will expand, with both production and consumption growing. The ever-increasing demand for it encourages producers to develop innovative technologies to increase pork production and improve its quality. Research limitations/implications. The scientific significance of the work is in the analysis of the main factors influencing the market of consumption of pork and forecasting the dynamics of changes in key indicators of its activity. As a conclusion, the necessity of intensification of state support of farms for growing pork and expansion of new external markets is presented. Originality/value. The practical significance of the research is to identify factors influencing the volume of sales of pork, contribute to increasing the competitiveness and efficiency of the meat market, which directly affects the development of the economy as separate regions and the country as a whole.